Analyzing The Risks of The Production Process in Light of Sustainable Business Using Fuzzy Logic: Menganalisis Risiko Proses Produksi dalam Rangka Bisnis Berkelanjutan Menggunakan Logika Fuzzy - Mohammed, Mohammed Ibrahim (Indonesian Journal of Law and Economics Review, 2024)
Production operations at the present time reflect a transition towards business sustainability and achieving a balance between human needs and environmental preservation. Accordingly, this study highlights the risks of production operations in light of sustainable business using fuzzy logic. To achieve this goal, previous studies were relied upon to identify risks. The production process, as well as identifying the factors influencing the production process in the organization. After that, 50 experts specialized in the field of production in Iraq were sought to find out their point of view on the risks of the production process and its consequences in Iraq. The results were analyzed using fuzzy logic and special risk matrices. (Easy, standard, difficult). The study revealed that the standard matrix is the best in confronting risks. Moreover, these risks must be faced effectively by adopting comprehensive strategies that combine environmental and economic performance, investing in technology and training, and ensuring the safety and health of workers, in a way that enhances this. Opportunities, reduce risks in production processes and contribute to achieving long-term sustainability. Highlights: Production sustainability requires balancing human needs and environmental preservation. Fuzzy logic identifies production risks, analyzed using expert insights and matrices. Strategies must enhance opportunities, reduce risks, and ensure long-term sustainability. Keywords: production risks, sustainable business, fuzzy logic.